Coffee Tourism Behavior in Chiang Mai Province, Thailand: Modern Marketing Perspectives in Coffee Shops - Madhyamapurush, Warach (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2024)
This paper reports on a study of coffee tourism behavior and seeks to: 1) discover the behavior of Thai tourists toward the use of coffee shops services in Chiang Mai; and 2) investigate the impact of the modern marketing perspectives of the 4E’s (experience, exchange, everyplace, and evangelism) on coffee tourism by reviewing the literature in this area. The data for this study were collected from Thai tourists who visited coffee shops in Chiang Mai. The descriptive and inferential statistics were used for the analysis of the data gathered. The results are as follows: most tourists who used the coffee shops in Chiang Mai are repeat customers. The media that influences the perception of tourists is personal social media or word of mouth. These tourists want the coffee shops should have a beautiful corner inside that is suitable for taking pictures. When considering the impact of demographic factors, there are important gender differences on the importance of choosing a coffee shop service by Thai tourists traveling to Chiang Mai during the COVID-19 pandemic.